Pre‐ and post evaluations of the effects of the Connect, Ask, Respond and Empathise (CARE) protocol on nursing handover: A case study of a bilingual hospital in Hong Kong. Issue 15 (25th April 2019) - Pun, Jack; Chan, Engle Angela; Man, Manbo; Eggins, Suanne; Slade, Diana
Abstract: Aims and objectives: To evaluate (a) the perceived effects of the training provided to nurses under a standardised Connect, Ask, Respond and Empathise (CARE) protocol; (b) the ability to enhance the effectiveness of the ISBAR checklist; (c) any increase in nurses' spoken interactions and/or improved comprehension of the patient conditions upon the transfer of responsibility. Background: Nursing handover is a pivotal act of communication with effects on both patient safety and risk management. Previous studies of critical incidents have highlighted ineffective communication, including a lack of interaction and incomplete and unstructured handovers, as a major contributor to patient harm. Design: A pre‐ and post evaluation study involving a questionnaire survey before and after the 3‐hours training. Methods: Forty‐nine randomly selected bilingual nurses with no previous professional development experience in handover communication were trained according to the CARE protocol, and their perceptions of nursing handovers were assessed before and after training using questionnaire. The STROBE checklist is used (See File S1). Results: Training of the CARE protocol improved key areas of the handover process. All participating nurses exhibited significant improvements in their perceptions of effective handover from before to after training. Particularly, improvements were observed in the interactive frequency and quality and completeness of the presented patient information per handover. Conclusions: The nurses reported a deeper understanding of their perceptions of handover after a patient‐centred intervention, a better quality of interactions (e.g., querying and checking by incoming nurses), a greater focus when managing handovers and a more complete and comprehensive transfer of information between nurses. Relevance to clinical practice: CARE protocol‐based training yielded significant improvements in nursing handover practice.